The incidence of coarse certification: Evidence from the ENERGY STAR Program - Sébastien Houde (ETH Zurich, CER-ETH - Center of Economic Research, 2018)
A coarse certification provides simple, but incomplete information about quality. Its main rationale is to help consumers trade off dimensions of quality that are complex and lack salience. In imperfectly competitive markets, it may induce excess bunching at the certification requirement, crowd out high quality, and facilitate price discrimination. Who will ultimately benefit from a coarse certification thus depends on the degree of market power firms can exercise as well as on consumers' sophistication in responding to such information. This paper illustrates these insights using the ENERGY STAR certification program as a case study. I investigate the incidence of the program with a structural econometric model of the U.S. appliance market. I find that the certification can crowd out energy efficiency, make consumers worst off, and have small, but heterogenous impacts on firms' profits. In this context, the certification tends to not be welfare-improving. This conclusion, however, crucially depends on the market environment and the design of the policy - in scenarios where energy prices are low, or the certification requirement is very stringent, the ES program can be welfare-improving.
Keywords: D43; L13; L15; L68; Q48; 330; Coarse certification; consumer attention; differentiated markets; structural estimation; energy efficiency